Body temperature programmable shape memory hybrids for comfort fittings: splints and insoles - Amin Fauzan Bin Abdullah (Nanyang Technological University, 2023)
This study focused on fabricating and testing shape memory hybrids, and a literature review on the subject was conducted. The shape memory hybrids used in this study were designed to provide a customisable fit for the user by changing their shape and mechanical properties in response to body temperature. The performance of the hybrids was evaluated through testing under various conditions, and the results showed their potential for use in comfort fittings. By adapting to the user's unique body shape, the programmable shape memory hybrids offer improved comfort and support compared to traditional materials. This study demonstrates the versatility and potential benefits of using shape memory hybrids in the development of wearable medical devices and other comfort fittings.